Ungrammaticality and descriptive adequacy in English pronunciation: the case of syncope - Gabor Turcsan (Anglophonia)
This paper looks at the grammar of a subset of vowel-zero alternations in English using findings from a large-scale descriptive project on syncope in contemporary spoken English. The data consist of 15 hours of casual conversations representing some 30 speakers illustrating three varieties (California, Lancashire & Ayrshire) and a reading task comprising 40 trisyllabic words with potential syncope sites. The quantitative analysis of the data indicates that more than half of the actually occurring cases of syncope are deemed to be impossible/faulty by the major pronunciation dictionaries thus ungrammatical. The paper addresses the question of how such a big gap seems to exist between descriptive grammar and usage by concentrating only on the ‘illicit’ cases. A closer qualitative analysis reveals interesting surface patterns: the deletion of the vowel does not lead to resyllabification i.e. destruction of structure but, following the computational principle of monotonicity, leaves behind phonetic traces that point to non-adjacency, clearly allowing speakers to reconstruct the vowel-full form. Traditional grammar seems to have a problem with emptiness and underlying non-adjacency while speakers seem to incorporate these easily in their grammar.